Dosimetric assessment and secondary cancer risk in breast radiotherapy: a Monte Carlo approach (Brazilian Journal of Radiation Sciences (BJRS), 2022)
To calculate the risk of secondary cancer induction resulting from this dose through a Monte Carlo simulation code and voxel-based anthropomorphic phantom to determine the radiation dose in organs and/or tissues with dosimetric importance and the effect of using static MLC in the 3D-CRT technique. In this work, a radiotherapy treatment of breast cancer was simulated using the radiation transport code MCNPX 2.7.0 and the adult anthropomorphic simulator FSTA_H50_M50. The absorbed doses for a set of organs with dosimetric importance were determined. A LINAC Varian 2100C device operated with two techniques was simulated: 2D with open field (OF) and 3D-conformational (3D-CRT), the latter with the use of a multilayer collimator (MLC) of the breast, both acting with 6 MV energy. The highest values of absorbed dose were obtained for the ipsilateral lung (7.22 Gy (3D-CRT) and 8.49 Gy (OF)) and the contralateral breast (6.29 Gy (3D-CRT) and 6.56 Gy (OF)), generating for these organs the greatest risks of secondary cancer induction. With the OF technique, due to the non-collimation of the beam, there was an increase in the absorbed dose in all organs compared to 3D-CRT, thus evidencing a more effective treatment with the 3D-CRT technique, improving both homogeneity and conformity with the dose absorbed in the target organ.